Tingkat Pengetahuan Kader Tentang SDIDTK di Desa Umbulmartani dan Desa Bimomartani Wilayah Puskesmas Ngemplak I Sleman - Christina Ririn Widianti (I Care Jurnal Keperawatan STIKes Panti Rapih, 2020)
Background: Children experience growth and development according to their stages. Early detection of growth and development deviations needs to be done. The implementation of early detection stimulation for child development (SDIDTK) has been carried out by Puskesmas officers and health cadres, but cadres do not routinely carry out it . Objective: The purpose of this study was to determine the level of knowledge of cadres about SDIDTK in Umbulmartani Village and Bimomartani Village in the Ngemplak I Health Center area. Methods: This research is a quantitative descriptive study with a population of cadres in the village of Umbulmartani and the village of Bimomartani. Samples were taken purposively and carried out on 133 cadres. Results: Less than half of the cadres were aged 41-50 years (44.36%) and a small proportion were 21-30 years old, while the rest were 31-40 years old and 51-60 years old. Kader 's latest education shows that more than half of the respondents have a high school education (73.68%) and 1 has an elementary education. SMP, and D3. Most of the cadres work as housewives (87.97%) and the rest work as teachers, midwives, entrepreneurs, farmers and civil servants. Cadre's level of knowledge about stimulation of early intervention detection of child development and development: a small proportion of them had less knowledge (8.27%) and more than half (74.44%) had sufficient knowledge. Conclusion: The level of knowledge of cadres about SDIDTK was still lacking as much as 8.27% and sufficient 74.44%